Profile of post operative cleft lip and palate in aceh cleft lip and palate center period of November 2018 - October 2019 - Syamsul Rizal (JKS (Jurnal Kedokteran Syiah Kuala), 2022)
Cleft Lip and Cleft Palate or Orofacial Cleft, which is known as the cleft lip is a condition of birth defects where an unusual opening or cleft is formed on the lips or palate.1 Cleft lip or labioschisis is a congenital anomaly that formed in the first trimester of pregnancy because of the mesoderm is not formed in that area so the nasal and maxillary processes that have been fused into a gap.2 Cleft lip can be caused by genetic and environmental factors.2 This study aims to determine the profile of post operative cleft lip and palate in Aceh Cleft Lip and Palate Center period of November 2018 - October 2019. Methods This study used a retrospective descriptive method by using the data that collected at the Aceh Cleft  Lip and Palate Center, in November 2018 - October 2019. The total number of patients that performed the surgery was 318 patients. Results From this study, presentation by sex: 173 male patients (54%), 145 female patients (46%). Presentation of cleft abnormalities experienced by the patients: Cleft lip 85 patients (27%), Cleft palate 64 patients (20%), Cleft lip and palate 169 patients (53%). Presentations for each type of surgery were: Cheilorrhaphy 131 patients (41%), Palatorrhaphy 109 patients (34%), and Rhinoplasty 78 patients (25%). While the presentation by the age limit according to the Cheilorrhaphy operation indication: Appropriate 71 patients (54%), Not appropriate 60 patients (46%), presentation by the age limit according to the Palatorrhaphy operation indication: Appropriate 57 patients (52%), Not appropriate 52 patients (48%). Conclusion From this study, it can be concluded that the most profile is male sex, cleft lip and palate, Cheilorrhaphy surgery and the corresponding for age limit of Cheilorrhaphy operation indication is appropriate, the corresponding for age limit of Palatorrhaphy operation indication is appropriate.